4(3k+7)-8(5k+1)=7(k-3)+6

Simple and best practice solution for 4(3k+7)-8(5k+1)=7(k-3)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3k+7)-8(5k+1)=7(k-3)+6 equation:



4(3k+7)-8(5k+1)=7(k-3)+6
We move all terms to the left:
4(3k+7)-8(5k+1)-(7(k-3)+6)=0
We multiply parentheses
12k-40k-(7(k-3)+6)+28-8=0
We calculate terms in parentheses: -(7(k-3)+6), so:
7(k-3)+6
We multiply parentheses
7k-21+6
We add all the numbers together, and all the variables
7k-15
Back to the equation:
-(7k-15)
We add all the numbers together, and all the variables
-28k-(7k-15)+20=0
We get rid of parentheses
-28k-7k+15+20=0
We add all the numbers together, and all the variables
-35k+35=0
We move all terms containing k to the left, all other terms to the right
-35k=-35
k=-35/-35
k=1

See similar equations:

| 5=72/y-7 | | 9x−4=5x+12 | | (4x-10)+(x+9)+(x-5)=180 | | 21=7(11-p) | | 7x-155=3x-35 | | 7(s-7)=35 | | 298=-0.0013x+1.8182 | | 8-1/4=12-1/2x | | 5+8x-2=-4x+22+6 | | –5d=–8d–6 | | y=0.15+50 | | Y=-3x^2-7x-1 | | 8x=+5=4x+7+2x | | -x-1-1-1-1-1-1-1-1=2 | | -1x-1x+x=4 | | x=33x-5=4x-9 | | 2x+20=3x,x | | `4x-9=39 | | 4x+26=2(2x+13 | | 3–12d=32d+4–dd= | | 2 (2x + 1)=  0.5 (2x − 14) | | 14x-80=40-6x | | 2(x+5)^2-16=0 | | F(x)=2x9 | | 14x-46=115-9x | | 28+28f=35+21f | | |8x|+17=-7 | | (Y+23)=63(2x-17) | | -0.6÷y=-2.3 | | 5x-2x=39 | | -9x+2=-7x=2 | | |6y-8|=-14 |

Equations solver categories